2018
DOI: 10.12688/wellcomeopenres.14861.1
|View full text |Cite
|
Sign up to set email alerts
|

The understanding of complex syntax in children with Down syndrome

Abstract: Background: Down syndrome (DS) is associated with poor language skills that seem disproportionate to general nonverbal ability, but the nature and causes of this deficit are unclear. We assessed how individuals with DS understand complex linguistic constructions, and considered how cognitive ability, memory and hearing level impact the ability of those with DS to process these sentence types. Methods: There were three groups participating in the study: children with DS (n = 33) and two control groups composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(80 reference statements)
1
12
0
Order By: Relevance
“…Particularly, concerning their syntactic ability DS individuals tend to produce shorter and less complex utterances compared to typically developing population (Rosin et al, 1988;Chapman et al, 1998;Price et al, 2008;Zampini & D'Odorico, 2011;Galeote et al, 2013;Frizelle et al, 2018), although advances in syntactic complexity may continue into late adolescence and young adulthood. It is also reported that DS group produced not only shorter, less complex utterances overall, but less complex noun phrases, verb phrases, and sentence structures, like questions and negations than did the TD group (Rosin et al, 1988;Chapman et al, 1998Chapman et al, , 2002Vicari et al, 2000;Chapman & Hesketh, 2000;Tsakiridou, 2006;Fabbretti et al, 1997;Stathopoulou, 2007;Price et al, 2007Price et al, , 2008Caselli et al, 2008;Zampini & D'Odorico, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Particularly, concerning their syntactic ability DS individuals tend to produce shorter and less complex utterances compared to typically developing population (Rosin et al, 1988;Chapman et al, 1998;Price et al, 2008;Zampini & D'Odorico, 2011;Galeote et al, 2013;Frizelle et al, 2018), although advances in syntactic complexity may continue into late adolescence and young adulthood. It is also reported that DS group produced not only shorter, less complex utterances overall, but less complex noun phrases, verb phrases, and sentence structures, like questions and negations than did the TD group (Rosin et al, 1988;Chapman et al, 1998Chapman et al, , 2002Vicari et al, 2000;Chapman & Hesketh, 2000;Tsakiridou, 2006;Fabbretti et al, 1997;Stathopoulou, 2007;Price et al, 2007Price et al, , 2008Caselli et al, 2008;Zampini & D'Odorico, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, difficulties emerged in subordination and in coordination, in relative clauses, in adverbial clauses, in finite clauses and in negated constructions (Rondal & Complain, 1996;Joffe & Varlokosta, 2007;Stathopoulou, 2007;Zampini & D'Odorico, 2011;Witecy & Penke, 2017;Polišenská et al, 2018). Additionally, they tended to use infrequently sentence complements, sentential embeddings, or compound sentences (Grela, 2002;Thordardottir et al, 2002;Frizelle et al, 2018). Obviously, the above difficulties increased with sentence length and grammatical complexity, but were also apparent in simple sentences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations